Relationship between body segment mass and running performance in well-trained endurance runners - Ueno, H.; Suga, T.; Takao, K.; Terada, M.; Nagano, A.; Isaka, T. (Journal of Applied Biomechanics, 2021)
This study examined the relationship between body segment mass and running performance in endurance runners. The total (muscle, fat, and bone masses), lean (muscle mass), and fat masses of the leg, arm, and trunk segments in 37 well-trained endurance runners were measured using dual-energy X-ray absorptiometer. The relative segment mass was calculated by normalizing the absolute mass to body mass. There were no significant correlations between absolute total, lean, and fat masses of all 3 segments and personal best 5000-m race time. No significant correlations were also observed between all 3 relative masses of the arm segment and personal best 5000-m race time. In contrast, medium positive correlations were observed between the relative total and lean masses of the leg segment and personal best 5000-m race time (r = .387 and .335, respectively, both P = .031). Furthermore, large negative correlations were observed between the relative total and lean masses of the trunk segment and personal best 5000-m race time (r = -.500 and -.548, respectively, both P = .002). These findings suggest that a mass distribution with smaller leg mass and greater trunk mass may be advantageous for achieving better running performance in endurance runners.